Inventory System Design Using Weight Average Cost (WAC) and Graphic Methods - Nurmaliana Pohan; Zulfitri Yani (Universitas Islam Kuantan Singingi, 2023)
Companies or business units are currently utilizing the role of the internet for company activities. Applications to support company activities that have been made have started to be web-based, both related to administration, finance, marketing and management of goods or inventory so that information can be obtained more quickly and easily accessed. wherever and whenever. However, until now there is no system that is able to manage data about inventory stock, for this reason the company wants to have a system that can be used to find out inventory, so that it can easily find out the amount and place to store inventory, that the inventory inventory system is not yet effective because doing data processing is still done in a way that is still manual. The results of the analysis are applied in an application capable of processing inventory system data using a web-based programming language. With the design of this new system, it is hoped that it will make it easier for companies/business units to process existing inventory system data, and can increase work effectiveness and efficiency.